2019
DOI: 10.7717/peerj.6593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of El Niño-Southern Oscillation 2015-2016 on the soluble proteomic profile and cytolytic activity of Millepora alcicornis (“fire coral”) from the Mexican Caribbean

Abstract: Reef-forming cnidarians are extremely susceptible to the “bleaching” phenomenon caused by global warming. The effect of elevated seawater temperature has been extensively studied on Anthozoans; however, to date the impact of thermal stress on the expression of genes and proteins in Hydrozoan species has not been investigated. The present study aimed to determine the differential proteomic profile of Millepora alcicornis, which inhabits the Mexican Caribbean, in response to the El Niño-Southern Oscillation 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 124 publications
1
29
3
2
Order By: Relevance
“…have been reported to be among the first cnidarians to lose their zooxanthellae symbionts during widespread bleaching events [134] and they have suffered local or regional extinctions from bleaching in the Pacific [78,85,135]. Numerous investigations of bleaching events on Caribbean and Florida Keys reefs have reported bleaching of Millepora colonies [133,[136][137][138][139], with M. alcicornis, a finely branched species, being the most severely affected reef corals. Such coral morphology has been described to be more susceptible to bleaching than encrusting and massive species [140].…”
Section: Bleaching Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…have been reported to be among the first cnidarians to lose their zooxanthellae symbionts during widespread bleaching events [134] and they have suffered local or regional extinctions from bleaching in the Pacific [78,85,135]. Numerous investigations of bleaching events on Caribbean and Florida Keys reefs have reported bleaching of Millepora colonies [133,[136][137][138][139], with M. alcicornis, a finely branched species, being the most severely affected reef corals. Such coral morphology has been described to be more susceptible to bleaching than encrusting and massive species [140].…”
Section: Bleaching Susceptibilitymentioning
confidence: 99%
“…Nevertheless, many studies have addressed the aetiology and effects of bleaching in Anthozoan species, wherein changes in the expression of genes and proteins were observed, and particularly heat shock proteins and transcription factors [154][155][156][157][158][159]. A recent study demonstrated that bleached specimens of M. alcicornis in Mexican Caribbean undergo a moderate decrease in symbiont's density and photosynthetic pigments, in addition to differential expression of 17 key proteins, such as calmodulin, actin and collagen often coupled with calcium homeostasis, exocytosis and cytoskeleton organization in Anthozoan species [139].…”
Section: Bleaching Susceptibilitymentioning
confidence: 99%
“…We found that the levels of 17 key proteins, tentatively identified as related to exocytosis, calcium homeostasis, cytoskeletal organization were modified in bleached M. alcicornis . Moreover, the protein levels of potential toxins, including a metalloprotease, a phospholipase A2 (PLA2), and an actitoxin were also altered [48]. It is obviously very important to continue studying the consequences of high water temperature on hydrocorals.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 66 marine natural products identified, 26 correspond to structures that were not previously reported. These 26 new chemical entities correspond to three aliphatic polyketides (1-3), one glycolipid (7), two diterpenes (15,16), two steroids (24,25), one triterpenoid saponin (40), and 17 conotoxins (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Figure 15 displays the overall biogenetic distribution of the reported compounds.…”
Section: Discussionmentioning
confidence: 99%